(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Introduction: Rett Syndrome (RTT) is a genetic disorder primarily seen in females that inhibits the use of a girl’s hands in everyday activities. A girl with RTT spends the majority of her day engaged in stereotypical hand wringing/mouthing movements at midline of the body. The probable cause behind the neurological effects of RTT is a mutation in the gene that encodes for methyl-CpG protein 2 (MeCP2). The hand wringing/mouthing behaviors preclude a girl with RTT from using the upper extremities in purposeful tasks such as school work, play skills, and other activities of daily living. Objectives: To develop a virtual reality (VR)-based therapeutic intervention that 1) decreases upper extremity stereotypies (repetitive movements that serve no function) that interfere with purposeful arm and hand use and 2) promotes purposeful, goal-directed arm function; improve upper extremity motor skills in girls with RTT. Materials and Methods: Using FAAST Software and Microsoft Kinect sensor, one girl with RTT participated in a 12-week IVR intervention (1 hour/session, 3 sessions/week, 36 total hours). Pre- and post-assessments were administered to examine any changes in upper extremity function. Results: The VR intervention led to improvements in use of the upper extremities to complete self-care activities, an increased number of reaches completed in a 15-minute period, and decreased time engaged in stereotypical hand movements. Conclusion: Future work will add additional support to determine the effectiveness of virtual reality as an intervention for girls with RTT.